Coated cysteamine, a potential feed additive for ruminants — An updated review - Muhammad Umar Yaqoob; Jia Hou; Li Zhe; Yingying Qi; Peng Wu; Xiangde Zhu; Xiaoli Cao; Zhefeng Li (Animal Bioscience, 2024)
For sustainable development, better performance, and less gas pollution during rumen fermentation, there is a need to find a green and safe feed additive for ruminants. Cysteamine (CS) is a biological compound naturally produced in mammalian cells. It is widely used as a growth promoter in ruminants because of its ability to control hormone secretions. It mainly controls the circulating concentration of somatostatin and enhances growth hormone production, leading to improved growth performance. CS modulates the rumen fermentation process in a way beneficial for the animals and environment, leading to less methane production and nutrients loss. Another beneficial effect of using CS is that it improves the availability of nutrients to the animals and enhances their absorption. CS also works as an antioxidant and protects the cells from oxidative damage. In addition, CS has no adverse effects on bacterial and fungal alpha diversity in ruminants. Dietary supplementation of CS enhances the population of beneficial microorganisms. Still, no data is available on the use of CS on reproductive performance in ruminants, so there is a need to evaluate the effects of using CS in breeding animals for an extended period. In this review, the action mode of CS was updated according to recently published data to highlight the beneficial effects of using CS in ruminants.